PENGARUH PENGGUNAAN MODUL TERHADAP KEMAMPUAN MULTIPEL REPRESENTASI SISWA PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN (Ksp) KELAS XI IPA SMA ADISUCIPTO SUNGAI RAYA - Ozi Auliza; Rizmahardian Ashari Kurniawan; Tuti Kurniati (Universitas Muhammadiyah Pontianak, 2019)
This study aimed to determine the ability and influence of student multiple representation module before and after using the module about solubility and solubility results in class XI IPA Adisucipto Sungai Raya High School. The research method used in this study was the Pre-experimental design method and the research design used was one-group pretest-posttest design. The sample in this study was the students of class XI IPA of Adisucipto Sungai Raya High School. Data collection techniques used in this research were measurement, observation and interview techniques. Meanwhile, data collection tools used multiple choice test questions, observation sheets and interview guidelines. Based on the results of data analysis, differences in the ability of student multiple representation were obtained the results of calculations with an average value of the representation aspect of macroscopic 75.00, microscopic 73.33, and symbolic 74.44. The effect of learning with multiple representation module was analyzed using the N-Gain formula. The results in the macroscopic aspect of 0.54, microscopic aspect of 0.68 and the symbolic aspect of 0.38 belong to the medium category.